Phenotypic and genotypic identification of lactic acid bacteria isolated from traditional pickles of the Çubuk region in Turkey - Bağder Elmacı, Simel; Tokatlı, Mehmet; Dursun, Derya; Özçelik, Filiz; Şanlıbaba, Pınar (Folia microbiologica, 2015)
A total of 152 lactic acid bacteria (LAB) were isolated from pickles produced in the Ankara-Çubuk region. These isolates were clustered into eight groups on the basis of their phenotypic characteristics including cell morphology, CO2 production from glucose, growth at 10 and 45 °C, growth in 6.5 % NaCl, and growth at pH 9.6. API 50 CH carbohydrate fermentation test, 16S ribosomal RNA (rRNA) sequence analysis, and sodium dodecyl sulfate-acrylamide gel electrophoresis (SDS-PAGE) whole-cell protein profile analysis were also performed for precise identification of the isolates at the species level. Molecular identification revealed that the most prevalent LAB species involved in pickle fermentation were Pediococcus ethanolidurans (46 isolates, 30.3 %), Lactobacillus brevis (37 isolates, 24.3 %), Lactobacillus plantarum (37 isolates, 24.3 %), and Lactobacillus buchneri (15 isolates, 9.9 %). Other LAB were found in minor frequencies such as Pediococcus parvulus (8 isolates, 5.3 %), Lactobacillus namurensis (6 isolates, 3.9 %), Lactobacillus diolivorans (1 isolate, 0.7 %), Lactobacillus parabrevis (1 isolate, 0.7 %), and Enterococcus casseliflavus (1 isolate, 0.7 %). When results of phenotypic and genotypic identification methods were compared, differences in the species distribution of LAB associated with pickles were defined between the API and the 16S rRNA sequencing. The API 50 CHL test coincided with the 16S rRNA results in 71 out of the 152 tested isolates, indicating that API gave unreliable identification results. A clear correlation could not be found between the results of whole-cell SDS profiles and 16S rRNA sequencing. Therefore, molecular characterization by 16S rRNA sequencing was considered to be the most reliable method for identifying isolates. The results presented in this work provide insight in to the LAB population associated with traditional Çubuk pickles and constitute a LAB strain resource for further studies involving the development of starter cultures.
Keywords: Lactic Acid; fenotyp; Phenotype; Turkey; Genotype; fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S; zelenina; Phylogeny; molekulární sekvence - údaje; Vegetables; fermentace; potravinářská mikrobiologie; Turecko; kyselina mléčná; DNA, Bacterial; DNA bakterií; Lactobacillaceae; Food Microbiology; Fermentation; RNA ribozomální 16S; Bacterial Typing Techniques; genotyp; Molecular Sequence Data